2007
DOI: 10.1021/jp066735t
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Polyelectrolytes in Thin Free-Standing Aqueous Films Resolved with Fluorescence Spectroscopy

Abstract: Pyrene labels are used as a molecular probe to investigate the rearrangement of polyelectrolytes confined in a free-standing aqueous film of progressively decreasing thickness. Monitoring the spectroscopic changes of covalently labeled poly(acrylic acid) in a surfactant-stabilized film, we followed the effects of confinement down to a film thickness of 15 nm. Already upon film formation at thicknesses of 50 nm, a marked increase of the excimer/monomer ratio was found irrespective of the degree of charge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Due to this oscillation of the polymer concentration within the film, it is suggested that the surfactant is unequally distributed over the polymer chains so that some of them become surface active again. 81 Comparing the foam film stabilities to the results of the surface tension and elasticity measurements, one can clearly see that the stability of the foam films is independent of the surface coverage. Concentration regimes with high surface coverage but low net charge show low stabilities, whereas in the regime with high surface tension and therefore low surface coverage, one can observe very stable films.…”
Section: Influence Of the Surface Charge On Foam Film Stabilitiesmentioning
confidence: 88%
“…Due to this oscillation of the polymer concentration within the film, it is suggested that the surfactant is unequally distributed over the polymer chains so that some of them become surface active again. 81 Comparing the foam film stabilities to the results of the surface tension and elasticity measurements, one can clearly see that the stability of the foam films is independent of the surface coverage. Concentration regimes with high surface coverage but low net charge show low stabilities, whereas in the regime with high surface tension and therefore low surface coverage, one can observe very stable films.…”
Section: Influence Of the Surface Charge On Foam Film Stabilitiesmentioning
confidence: 88%
“…This leads to an extremely broad concentration regime (up to three orders of magnitude) [ 37 , 51 ] where the chains are overlapped, but not entangled. It has been suggested that some anisotropic, layer-like structures may be formed in such systems [ 51 – 53 ], which poses additional difficulties for universal description of transport properties of such systems. Moreover, if no measures are taken to remove carbon dioxide, the solutions are not actually salt-free [ 44 ], which may be a source of experimental errors.…”
Section: Introductionmentioning
confidence: 99%
“…Rapoport et al recently reported that a transition may occur between a lateral layer structure and a network structure. 36 In both cases, the interchain distance in semidilute regime (c > c*) scales with the concentration 2,26,27,29,37−41 as c −1/2 , and it corresponds to the mesh size of the transient network.…”
Section: Introductionmentioning
confidence: 98%
“…Overlapping leads to a transient network in the unentangled-semidilute regime. , Milling and Kendall, Thedoly et al, and Jönsson et al proposed a parallel aligned lateral layers instead of a network structure. Rapoport et al recently reported that a transition may occur between a lateral layer structure and a network structure . In both cases, the interchain distance in semidilute regime ( c > c *) scales with the concentration ,,,, as c –1/2 , and it corresponds to the mesh size of the transient network.…”
Section: Introductionmentioning
confidence: 99%